NEW PALEOMAGNETIC DATA ON THE EARLY CAMBRIAN OF WEST SAYAN - Kazanskii A.Yu.; Metelkin D.V.; Kungurtsev L.V.; Lavrenchuk A.V. (My University, 1999)
New paleomagnetic data on the Early Cambrian of the north of West Sayan are presented. The magnetic properties of rocks of the Lower Monok and Upper Monok Formations are investigated. Mineral compositions of major carriers of magnetization are revealed. Two ancient components of ChRM are recognized. The first component. A, (Ds = 121°, Is = 28°, α95 = 4.9°) is the closest to primary magnetization, which is supported by positive fold and baked-contact tests. It is probably of Early Cambrian age. The second component B (Ds = 114°, Is = -15°, α95 = 13.1°) is synfolding and apparently related to the Upper Cambrian-Ordovician overprint. On the basis of the obtained paleomagnetic data it is shown that in the Early Cambrian the North-Sayan and Kurtushiba terranes composed a uniform paleoisland-arc system, which was formed at a distance of more than 1500 km north of the northern (in the ancient coordinates) frame of the Siberian continent, within 10-20°N. In the Early-Middle Cambrian this system moved southward (in the ancient coordinates) without any significant rotation.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская